2006
DOI: 10.1111/j.1464-410x.2006.06074.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in characteristics of nocturnal enuresis between children and adolescents: a critical appraisal from a large epidemiological study

Abstract: OBJECTIVE To evaluate any differences in the characteristics of primary nocturnal enuresis (PNE) between younger enuretic children and adolescents. SUBJECTS AND METHODS In all, 21 000 questionnaires designed to determine the presence or absence of bed‐wetting, diurnal incontinence, frequency of wetting, systemic illness, and family history, were sent to children aged 5–19 years from 67 kindergartens, primary schools and secondary schools randomly selected by a computer from different areas in Hong Kong. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
99
1
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(134 citation statements)
references
References 28 publications
20
99
1
14
Order By: Relevance
“…The prevalence has been found to be 20-25% in children aged 4 years old. While the prevalence is 10-15% at the age of 5-7 years, it decreases to approximately 0.5-2.2% at the age of 15 years and older by showing spontaneous recovery each year with a rate of approximatley 15% (4)(5)(6). In the studies performed in our country, the prevalence has been reported to be 11.5-12.4% between the ages of 6 and 16 (7,8).…”
Section: Epidemiologymentioning
confidence: 80%
See 2 more Smart Citations
“…The prevalence has been found to be 20-25% in children aged 4 years old. While the prevalence is 10-15% at the age of 5-7 years, it decreases to approximately 0.5-2.2% at the age of 15 years and older by showing spontaneous recovery each year with a rate of approximatley 15% (4)(5)(6). In the studies performed in our country, the prevalence has been reported to be 11.5-12.4% between the ages of 6 and 16 (7,8).…”
Section: Epidemiologymentioning
confidence: 80%
“…Many studies related to the prevalence of nocturnal enuresis have been performed in our country and abroad (4)(5)(6)(7)(8)(9). The prevalence has been found to be 20-25% in children aged 4 years old.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la enuresis moderada (3-6/semana) o grave (diaria) y la que persiste a los diez años, difícilmente se resolverá sin tratamiento 7 . Independientemente de la gra- Usualmente el objetivo buscado es la curación, que significa sequedad completa definitiva tras finalizar el tratamiento.…”
Section: Tratamiento De La Enuresis Primaria Monosintomáticaunclassified
“…In the latter type, enuretic alarm treatment should be considered initially, and it is then important to investigate whether a respiratory obstruction is present in patients with nocturnal polyuria, whether the patient is constipated, and whether patients with non-monosymptomatic nocturnal enuresis have lower urinary tract symptoms or attention deficit hyperactivity disorder. [7]. (A) If patients take the desmopressin after 8 p.m. in them who sleeps at 9 p.m., they will be able to fully exercise the effect of the drug because the time of the effect of the desmopressin is included during the sleeping time.…”
mentioning
confidence: 99%